The impact of object orientation during 3D printing on part quality - Nehrub , S.L.; Bonchuk , S.V.; Herasymchuk , A.P. (Theory and Practice of Metallurgy, 2025)
Purpose. Research and practical evaluation of the impact of part placement on the table during 3D printing on material consumption, printing time, and quality of mechanical engineering parts. Methodology. Practical tests were conducted in real production conditions with a preliminary assessment of printing results in the Ultimaker Cura 5.8.1 software environment and subsequent printing of the part in a 3D printer ANYCUBIC PHOTON M3 MAX. Originality and Findings. A practical study of real 3D printing of parts with photopolymer resin was conducted after analyzing various options for the location of the 3D model on the build plate. Rational positions for 3D models in space were experimentally determined to reduce printing time, material consumption, and eliminate 3D printing defects. An assessment of the influence of the location of parts on the table during 3D printing with white photopolymer resin ESUN Hard-Tough Resin on material consumption, printing time, and quality of mechanical engineering parts was performed. A significant influence of the location of the model on the build plate - namely at an angle - on the printing quality of individual elements of parts, especially small ones, on the amount of material consumed, and printing time was recorded. Practical value. The conducted research allowed us to more consciously place 3D models on the build plate, pre-estimate the material costs for supports and edit the position of the model in case of an unsuccessful choice, thereby reducing printing time and the number of losses due to printing defects due to the lack of supports. Gaining practical experience in 3D printing and forming practical recommendations, which allowed us to improve the state of 3D production at the enterprise.